2021
DOI: 10.1126/sciadv.abe5735
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging systems biology for predicting modulators of inflammation in patients with COVID-19

Abstract: Dysregulations in the inflammatory response of the body to pathogens could progress toward a hyperinflammatory condition amplified by positive feedback loops and associated with increased severity and mortality. Hence, there is a need for identifying therapeutic targets to modulate this pathological immune response. Here, we propose a single cell–based computational methodology for predicting proteins to modulate the dysregulated inflammatory response based on the reconstruction and analysis of functional cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…In addition, versican itself has the ability to affect inflammatory cytokine release in stromal cells and immune cells, therefore appropriate cytokine-mediated versican production may promote the next inflammatory response (55). In this case versican acts as a TLR2 agonist; stimulating TLR2 and its co-receptors TLR6 and CD14 to release pro-inflammatory molecules such as TNFa and IL-6, inducing macrophage activation (81)(82)(83)(84)(85). This positive feedback loop leads to prolongation of an inflammatory environment.…”
Section: Versican Alters Immune Phenotypementioning
confidence: 99%
“…In addition, versican itself has the ability to affect inflammatory cytokine release in stromal cells and immune cells, therefore appropriate cytokine-mediated versican production may promote the next inflammatory response (55). In this case versican acts as a TLR2 agonist; stimulating TLR2 and its co-receptors TLR6 and CD14 to release pro-inflammatory molecules such as TNFa and IL-6, inducing macrophage activation (81)(82)(83)(84)(85). This positive feedback loop leads to prolongation of an inflammatory environment.…”
Section: Versican Alters Immune Phenotypementioning
confidence: 99%
“…Innate immunity relies on pattern recognition receptors (PRRs) by multiple cell surfaces or intracellular receptors and responds by signal transduction to effector molecules [ 94 , 95 ]. SARS-CoV-2 infection activates pattern recognition receptors on pulmonary epithelial cells, endothelial cells, macrophages, DCs, and other immune cells to produce cytokines [ 96 , 97 ]. Recognition receptors including Toll-like receptors (TLRs), retinoic acid-inducible gene I (RIG-I, melanoma differentiation-associated gene 5 (MDA5), cyclic guanosine phosphate adenosine phosphate synthase (cGAS), stimulator of interferon genes (STING), and nucleotide-binding oligomerization domain-like receptors (NLRs) play a significant role in antiviral defense against coronaviruses ( Figure 3 ) [ 98 , 99 , 100 ].…”
Section: Ace2 Sars-cov-2 and Innate Immune Pathwaysmentioning
confidence: 99%
“…In contrast, a recent study by Boyd et al (2020) demonstrated that expression of ADAMTS4 in lung fibroblasts was associated with immunopathology and poor disease outcomes in mice and humans ( Boyd et al, 2020 ). Furthermore, systems biology approaches have indicated that overexpression of versican, an ADAMTS enzyme substrate, may be associated with hyperinflammatory responses following severe COVID-19 infection ( Jung et al, 2021 ). These findings suggest that ADAMTS enzymes and related pathways may be attractive therapeutic targets and further investigation is warranted.…”
Section: Therapeutic Potential Of the Extracellular Matrixmentioning
confidence: 99%